Unexpected ortho-Heck Reaction under the Catellani Conditions - Rago, Alexander J. (Org Lett, 2020)
An unexpected ortho-Heck reaction has been discovered during the study of palladium/norbornene (Pd/NBE) catalysis. Under the Catellani reaction conditions in the presence of lithium salts and olefins, Heck coupling takes place at the ortho position instead of the commonly observed ipso position; meanwhile, a norbornyl group is introduced at the arene ipso position. Systematic deuterium labeling and crossover experiments suggest an unusual 1,4-palladium migration/intramolecular hydrogen transfer pathway. The knowledge gained in this study could provide insights for the future development of the Pd/NBE catalysis.